#1**+1 **

This is the original equation:

\(96\pi = 24\pi+x(\frac{4}{3}\pi*27)\)

We want to solve for x here:

\(96\pi = 24\pi+x(\frac{4\pi}{3}*27)\) | First, evaluate what is in the parentheses. \(\frac{4\pi}{3}*27\) |

\(\frac{4\pi}{3}*27=\frac{4\pi}{3}*\frac{27}{1}=\frac{108\pi}{3}=36\pi\) | Reinsert this back into the original equation. |

\(96\pi=24\pi+36\pi x\) | Subtract \(24\pi\) on both sides of the equation. |

\({72\pi=36\pi x}\) | Divide both sides by the GCF of \(72\pi\) and \(36\pi x\). The pi will cancel out and the GCf of 72 and 36 is 36. Therefore, divide both sides by 36*pi. |

\(\frac{70\pi}{36\pi}=\frac{36\pi x}{36\pi}\) | Simplify both sides of the equation. |

\(2=x\) | x is already isolated, so we are done! |

We're done now! Yes!

TheXSquaredFactor
Jul 31, 2017